Implementing the Digital Economy Enabling Environment Guide: A Case Study from Indonesia - Pingkan Audrine; Arumdriya Murwani (Center for Indonesian Policy Studies (CIPS), 2021)
Indonesia's digital economy is predicted to grow to reach USD124 billion in 2025 but this huge potential would only be realizable with the support of an adequate regulatory framework. The Center of Indonesia Policy Studies has conducted a series of research and advocacy to define the steps that could be taken to support the growth of the digital economy ecosystem in Indonesia. In this regard, CIPS made use of a handbook from the Center for International Private Enterprise (CIPE) to conduct its research and advocacy, focusing on four main aspects – consumer protection, data protection, cybersecurity, and electronic transactions. This paper is a case study in the usage of this guidebook in the context of the Indonesian digital economy and also describes how CIPS carried out its research using the interview method and through the holding of Digital Week 2020.
Keywords: 330; Coregulation; Digital Economy; Indonesia's digital economy; Center for International Private Enterprise; CIPE; Implementing the Digital Economy Enabling Environment Guide; Digital Economy Case Study; digital economy policy; public private dialogue; cyber security; e-payment; data privacy; regulatory sandbox; co-regulating; internet; digital platforms; Indonesia content moderation; content moderation; user-generated content; indonesia social media; MOCI; ministry of communication and informatics; digital content; social modia content; indonesia social media content; internet sharing; sharing content through internet; MOCI regulation no 5/2020; electronic system organizer; indonesia electronic system organizer; social media regulation; freedom of expression